2019 Pasir Gudang Chemical Incidents: The Impact of Transdisciplinary Approach on Emergency Medical Services - Rahmat, Rashdan (Universitas Gadjah Mada, 2025)
Introduction: Managing mass casualty incidents (MCI) is always challenging, requiring a well-coordinated transdisciplinary approach (TDA) due to its complexity. Between 7th and 20th March 2019, a state-level chemical incident occurred in Pasir Gudang’s heavily industrialized area. Illegal dumping of tonnes of waste into Kim Kim River released a mix of volatile organic compounds (VOCs), including acrolein, acrylonitrile, and benzene, causing mainly respiratory and gastrointestinal symptoms. Objective: To coordinate an effective response to the Kim Kim chemical incident. Methods: Government agencies, industrial players, and NGOs collaborated under the coordination of Malaysia’s National Disaster Management Agency (NADMA), following Directive No. 20 of the National Security Council. Key agencies such as the Department of Environment, Fire and Rescue Department, Ministry of Health, and Johor State Disaster Management Committee, with support from Pasir Gudang Emergency Mutual Aid (PAGEMA), led containment efforts. A patient management center was established near the site to prevent overwhelming healthcare facilities. Ambulance transportation and logistics were systematically organized. Results: Approximately 6,000 victims, including medical staff, received treatment over the two-week period. The coordinated effort effectively contained the incident. Conclusions: The incident highlights the importance of public-private partnerships and shared understanding among agencies in managing complex disasters through TDA.